PENGARUH SMART TV SEBAGAI MEDIA PEMBELAJARAN VISUAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA KELAS X SMAN 30 BONE - niar, Yuniar,S; A. Kasmawati; Jusman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Yuniar S. 2026. The Effect of Smart TV as a Visual Learning Media on Students’ Learning Outcomes in Informatics Subject at Grade X of SMAN 30 Bone. Supervised by Hj. A. Kasmawati, S.P., M.M. and Jusman, S.Pd., M.Pd. The main problem of this study was to determine whether the use of Smart TV as a visual learning medium affects students’ learning outcomes in Informatics subject at Grade X of SMAN 30 Bone. This study aimed to examine the effect of Smart TV as a visual learning medium on students’ learning outcomes. This research employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The population consisted of all Grade X students of SMAN 30 Bone totaling 60 students. A saturated sampling technique was applied, in which the entire population was used as the research sample. The research instrument was a learning achievement test administered through pretest and posttest. Data were analyzed using descriptive and inferential statistics, including normality tests, homogeneity tests, and an independent sample t-test. The findings revealed that the use of Smart TV as a visual learning medium had a significant effect on students’ learning outcomes. This was indicated by the significance value (Sig. 2-tailed) of 0.000, which was lower than 0.05. Furthermore, the mean score of the experimental class was 90.00, which was higher than that of the control class at 81.72. Therefore, it can be concluded that the use of Smart TV as a visual learning medium effectively improves students’ learning outcomes in Informatics subject at Grade X of SMAN 30 Bone.